Multicomponent, nonpharmacological delirium interventions for older inpatients - Eckstein, Claudia; Burkhardt, Heinrich (Zeitschrift für Gerontologie und Geriatrie, 2019)
BackgroundOlder people represent a risk group for acquiring or further development of delirium during hospitalization, therefore requiring suitable nonpharmacological delirium interventions.ObjectiveThis scoping review analyzed nonpharmacological intervention programs for older inpatients with or without cognitive decline on regular or acute geriatric wards to present the range of interventions.MethodsA systematic literature search was conducted using scientific databases. A total of 4652 records were screened by two independent reviewers, leaving 81 eligible articles for full-text screening and 25 studies were finally included. Inclusion criteria were older patients ≥65 years in regular or acute geriatric wards and nonpharmacological multicomponent interventions.ResultsMore than a half of the included studies (14, 56%) recruited patients with pre-existing cognitive decline as part of the study population and 12% focused exclusively on patients with cognitive decline. On average 11 intervention components were integrated in the programs and two programs included full coverage of all 18 identified components.ConclusionOnly few programs were described for older inpatients and even fewer regarding pre-existing cognitive decline. The low numbers of interventions and data heterogeneity restricted the assessment of outcomes; however, delirium incidence, as reported by two thirds of the studies was reduced by nonpharmacological multicomponent interventions.